FESTIVAL BUDAYA ISEN MULANG SEBAGAI UPAYA PROMOSI PARIWISATA BUDAYA DI PROVINSI KALIMANTAN TENGAH - Saputra, Putu Wisnu; Suparta, Ida Kade (Institut Agama Hindu Negeri Gde Puda Mataram, 2023)
This study uses a qualitative approach to obtain clear descriptions related to the implementation of the Isen Mulang cultural festival as an effort to promote cultural tourism. Isen Mulang is an annual agenda for the Palangkaraya tourism office as a series of activities to celebrate the anniversary of Central Kalimantan Province. As a result of the Covid-19 pandemic, the Isen Mulang cultural festival has not been held for two years considering that all Indonesian people, especially Central Kalimantan, have restricted their activities. With several considerations, finally in 2022 this activity will be held again in the City of Palangka Raya with the theme